CD44 expression in normal adrenal tissue and adrenal tumours. Issue 1 (January 1998) - Barshack, I; Goldberg, I; Nass, D; Olchovsky, D; Kopolovic, J
Abstract : BACKGROUND: CD44 is a cell surface glycoprotein found on many normal cells, mainly lymphoid and epithelial. Normal cells usually express standard CD44 (CD44-S), whereas malignant tumours may express CD44 variant isoforms (CD44-V). CD44 expression has been described for neural crest derivatives. Characterisation of differences in CD44 expression may help in the diagnosis and differentiation of distinct adrenal tumours. AIMS: To examine CD44 expression in different layers of cortical cortex, in adrenal medulla, and in adrenal tumours. METHODS: CD44-S and CD44-V6 expression were studied in 12 cases of adrenal cortical adenoma, 3 of adrenal cortical carcinoma, 10 of pheochromocytoma, and 4 normal adrenal glands. RESULTS: CD44-V6 staining showed cytoplasmic expression in normal adrenal cortex and in cortical adenomas and carcinomas. Pheochromocytomas also showed CD44-V6 expression but in 5 of the 10 cases it was sparse, focal, and sometimes perinuclear. Strong membranous staining for CD44-S was observed in normal adrenal medulla. Analysis of CD44-S expression revealed differences between cortical adrenal tumours and pheochromocytomas. Ten of 12 cortical adenomas and 2 of 3 cortical carcinoma cells showed weak to moderate cytoplasmic staining, but all cases of pheochromocytoma had strong membranous staining. CONCLUSIONS: Membranous CD44-S staining may help to distinguish pheochromocytoma from adrenal cortical adenoma.